PERBANDINGAN EFEKTIVITAS TERAPI PANAS DAN ENDORPHIN MASSAGE TERHADAP INTENSITAS NYERI KALA I FASE AKTIF PERSALINAN NORMAL IBU PRIMIPARA - Wahyuni, Tengku Sri; Purba, Juliani; Batubara, Ardiana (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Labor pain can cause stress which causes the release of excessive hormones such as catecholamines and steroids. Pain in labor can also cause hyperventilation so that oxygen needs increase, increase blood pressure, and decrease intestinal motility and urinary vesicles. Heat Therapy and Endorphine Massage is a non-pharmacological method that is thought to be effective in reducing labor pain. The purpose of this study was to compare the effectiveness of heat therapy and endorphin massage on the intensity of pain in the first active phase of normal labor in primiparous mothers at the Pematangsiantar city BPM. The type of research used is quasi-experimental. The population of this study was primiparous maternity during the active phase I who experienced normal labor in the Pematangsiantar City Independent Practice Midwife. The research sample consisted of two groups of 20 respondents each taken by purposive sampling technique, and certain inclusion criteria. The sampling technique was accidental sampling in April - June 2015, through interviews using questionnaires and the scale of pain measurement numerical rating scales (NRS). Analysis of the data used with T-Test on normal distributed data using Wilxocon and U Mann Whitney on data with abnormal distribution. The technique of heat therapy and endorphine massage is a non-pharmacological therapy that can reduce pain intensity during the first active phase of labor. There is the influence of heat therapy and endorphine massage on pain intensity during the first active phase in primiparous mothers with a value of p = 0.001. There is no difference in the effectiveness of heat therapy and endorphine massage techniques in reducing pain intensity during the first active phase in primiparous mothers. Midwives should be able to apply heat therapy techniques and endorphine massage to reduce pain intensity during the first active phase of labor and can also teach it to family / childbirth assistants. Keywords: Heat Therapy, Endorphin Massage, First Pain Intensity, Active Phase of Normal Labor, Primipara Mother